Internal evaluation in Faculty of Nursing and Midwifery, Tehran University of Medical Sciences - Parsa Yekta Z; Salmaani Barough N; Monjamed Z; Farzianpour F; Eshraghian M (Tehran University of Medical Sciences, 2005)
Introduction: Evaluation is a systematic process for collecting, analyzing and interpretation of the obtained information for the purpose of investigating how much the objectives in mind can be achieved. Education in an academic educational system means bringing about proper and increasing changes that affect the outcome of this system, that is affecting the students, and the aim of such evaluation was promotion of the quality of an education process. Materials and Methods: In this study faculty of nursing and midwifery, Tehran University of Medical Sciences, benefiting from opinion poll of university lectures, student and graduates have evaluated their system of educational in the year 2004 and their aim was to remodel and adjust educational system with the society's needs and promotion of the quality of such education's. The employed method was cross sectional and descriptive and analytical on the basis of 10 procedural steps and with in 8 sections dealing with evaluated factors. Such as faculty board members, management and organizational capability, students, manpower and logistic affairs, educational environments research work centers, health and therapeutic sections, educational equipment, research equipment, laboratory and diagnosis centers, educational courses and programs, teaching and learning process as well as satisfaction expressed by students. Results: the results of the research showed that general average of 8 investigating sections, based on SWOTs model were respectively 80.4% (nursing department), 81.5% (Midwifery department) and 82.1% (Ph.D nursing) that may well be interpreted as a desirable research work. Conclusion: Educational evaluation is the best indicator showing how much we should go to achieve certain aims, analyzes quality of the activity if such a system and by which we achieve logical and routine results.